Spotlight on Rural Nurses: Implications for a New Nursing Discipline in Jordan - Karen Francis; Hani Nawafleh; Ysanne Chapman (Rural Nurse Organization; Binghamton University, 2012)
This ethnographic study sought to provide a snapshot of rural nurses' practice in comprehensive primary health care centres (CPHCCs) in Jordan. These nurses provide a vital service to local populations although it is recognised that the nursing workforce is predominantly secondary level (e.g. practical nurses and aide nurses). The findings indicate that educational preparation, skill-mix, access to professional development, the lack of collegiate support, nursing practice standards, ineffective management, poor distribution of health resources and geographic isolation are important factors impacting on the CPHCC nurses' practice. The study highlights the need for improved resourcing of the CPHCCs and advocates immediate action by the Ministry of Health (MoH) and senior nursing administration to support the development of rural nursing. In addition, it is recommended that effective recruitment and retention strategies to address the nursing shortage and improve the nursing skill-mix be developed.